2004
DOI: 10.1089/107632704323061807
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Development of Biomimetic Polymers by Protein Immobilization: PEGylation of Insulin as a Model Reaction

Abstract: Many current tissue-engineering investigations aim at the rational control of cell adhesion and tailored composition of biomaterial surfaces by immobilizing various protein and peptide components, such as growth factors. As a step on the way to develop polymers that allow for such surface modifications, water-soluble polymers were used as model substances to examine reactions with proteins containing amine groups. Consequently, the uncommon PEGylation of insulin in aqueous buffers was used to characterize reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Some studies using the spacer chains were performed and the increase in the activity is reported. 26,[29][30][31][32]48 However, possible implications of steric hindrance in spacing growth factor from the substrate and the possible impact on growth factor binding to its cell surface receptor should be taken into consideration. In fact, the POE conjugation reduced the biological activity of insulin.…”
Section: Spacer Insertion and Surface Stiffnessmentioning
confidence: 99%
“…Some studies using the spacer chains were performed and the increase in the activity is reported. 26,[29][30][31][32]48 However, possible implications of steric hindrance in spacing growth factor from the substrate and the possible impact on growth factor binding to its cell surface receptor should be taken into consideration. In fact, the POE conjugation reduced the biological activity of insulin.…”
Section: Spacer Insertion and Surface Stiffnessmentioning
confidence: 99%
“…9,10 Much effort has been devoted to ensure the stable localization of bioactive molecules, using either physical adsorption or chemical crosslinking methods. 15,24 Physical adsorption using soluble growth factor may not be sufficient in promoting long-term implantation due to factors such as protein desorption and/or exchange with physiologic fluid contact. In contrast, chemical binding involves a covalent attachment of the target molecule to the solid surface, thereby resulting in irreversible binding with high levels of surface coverage, and making this approach more suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, lubricating drops containing polyethylene glycol 400 are available as ready-to-use. Such solutions tend to be stable, have reduced risk of proteolysis, and have minimal potential for antigenicity and impact on the patient’s immune system [ 35 , 36 ]. Additionally, the polyethylene glycol in available lubricating drops can accelerate epithelial defect healing [ 37 ].…”
Section: Solvent and Storagementioning
confidence: 99%